Oxymatrine Attenuates Osteoclastogenesis via Modulation of ROS-Mediated SREBP2 Signaling and Counteracts Ovariectomy-Induced Osteoporosis - Chao Jiang (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis, mainly caused by osteoclast-induced bone resorption, has become a major health problem in post-menopausal women and the elderly. Growing evidence indicates that inhibiting osteoclastogenesis is an efficient approach to develop alternative therapeutic agents for treating osteoporosis. In this study, we identified the potential regulating role of Oxymatrine (OMT), a quinazine alkaloid extracted from Sophora flavescens with various therapeutic effects in many diseases, on osteoclastogenesis for the first time. We found that OMT attenuated RANKL-induced osteoclast formation in both time- and dose-dependent manners. Further, OMT significantly suppressed RANKL-induced sterol regulatory element-binding protein 2 (SREBP2) activation and the expression of the nuclear factor of activated T cells 1 (NFATc1). Moreover, OMT inhibited the generation of RANKL-induced reactive oxygen species (ROS), and the upregulation of ROS could rescue the inhibition of SREBP2 by OMT. More importantly, ovariectomy (OVX) mouse model showed that OMT could effectively improve ovariectomy (OVX)-induced osteopenia by inhibiting osteoclastogenesis in vivo. In conclusion, our data demonstrated that OMT impaired ROS mediated SREBP2 activity and downstream NFATc1 expression during osteoclastogenesis, suppressed OVX-induced osteopenia in vivo, which suggested that OMT could be a promising compound for medical treatment against osteoporosis.